High-temperature-resistant electromagnetic shielding graphene film as well as preparation method and application thereof
Through the assembly of benzoxazine and graphene with conjugated structure, the problems of poor flexibility, poor heat resistance and poor electromagnetic shielding performance of graphene film materials were solved, and high orientation, excellent conductivity and electromagnetic shielding performance were prepared. high temperature resistant graphene film material.
Patent Information
- Application Number
- CN202411946126.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-02-21
AI Technical Summary
The existing graphene film materials have poor flexibility, poor heat resistance and difficulty in effectively shielding electromagnetic waves.
The mass ratio of graphene to benzooxazine through the conjugated structure is 2:1-1:2. Self-assembly and conjugated diene and graphene on the thiophene ring are self-assembly using conjugation and self-conjugated diene and graphene on the thiophene ring The DA reaction between the substituted olefins on the film improves the orientation and performance of the film material.
The prepared high-temperature resistant electromagnetic shielding graphene film material has high orientation, excellent conductivity, electromagnetic shielding and toughness, and is suitable for the preparation of high-performance electromagnetic shielding materials. It can have a carbon residue ratio of more than 75% at 800°C. , has excellent flame retardant properties.
Smart Images

Figure CN119490725A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of composite film, and in particular relates to a high temperature resistant electromagnetic shielding graphene film and a preparation method and application thereof. Background Art
[0002] The development of the fifth generation of communication technology (5G) has driven the demand for higher integration, densification and miniaturization of silicon chips. In 5G RF modules, to ensure that the system-level package works properly at high frequencies, it is necessary to use partitioned electromagnetic interference (EMI) shielding to isolate signals between different functional areas to avoid damage to precision devices. In addition, it is also very important to consider secondary pollution issues during the development process and pursue lightweight and highly stable electromagnetic shielding materials.
[0003] Polybenzoxazine is usually a ring-opening polymer of benzoxazine monomers. It has a cross-linked network structure, similar to phenolic resin, and is a new type of thermosetting resin. The typical benzoxazine molecular structure contains C, O, N and H elements. Due to its special molecular design flexibility, various raw materials can be used to synthesize benzoxazine. This molecular characteristic gives benzoxazine resin many excellent properties. It has good flame retardant properties, can be polymerized without adding catalysts, has excellent thermal stability, high mechanical properties, almost zero volume shrinkage during curing, and low surface free energy. These advantages make benzoxazine resin have broad application prospects in new energy vehicles, electronic information, aerospace, and electrical insulation.
[0004] Graphene is a single-layer structure composed of sp2-hybridized carbon atoms connected to each other. It has a high aspect ratio and specific surface area, excellent electrical conductivity and dielectric loss coefficient. Therefore, it has been widely used in functional composite materials to achieve excellent electromagnetic interference shielding performance and conductivity. Based on the controllable preparation characteristics of graphene in size and structure, graphene structures of different dimensions can be prepared through appropriate formulation design and process treatment. When two-dimensional or three-dimensional graphene is dispersed in a polymer matrix, a three-dimensional conductive network is formed, which not only improves the conductivity of the composite material but also enhances the EMI shielding effect. The existing shielding materials are limited in application due to their high density, high mass and narrow shielding frequency band, so "thin, light, wide and strong" electromagnetic shielding materials are needed. Chinese patent CN117004179A discloses a high temperature resistant graphene film material and its preparation method and application. In the thienyl-containing benzoxazine / graphene film system prepared by the present invention, graphene and benzoxazine are first self-assembled by conjugation, and then further combined by DA reaction between conjugated diene on the thiophene ring and substituted olefin on graphene, so that the orientation degree of the film material is improved, giving the material excellent thermal conductivity and toughness and other properties. After curing, the composite material has a residual carbon rate of more than 75% at 800°C, has excellent flame retardancy, is suitable for preparing high-performance thermal conductive materials, and can be used for electronic components or battery heat dissipation of new energy vehicles. Chinese patent CN116987362A also discloses a benzoxazine resin-based graphene film material and its preparation method and application. The film material is formed by thienyl-containing benzoxazine and graphene, and the graphene film material prepared by it can be used for electronic components or battery heat dissipation of new energy vehicles. However, the electromagnetic shielding performance of the resin-based graphene film material prepared in the prior art is general. Summary of the invention
[0005] Purpose of the invention: In order to solve the above-mentioned technical problems, the present invention aims to provide a high-temperature resistant electromagnetic shielding graphene film material. The electromagnetic shielding graphene film material of the present invention has a high degree of orientation, excellent conductivity, electromagnetic shielding and toughness, and is suitable for preparing high-performance electromagnetic shielding materials. It effectively solves the current problems of poor flexibility, poor heat resistance and difficulty in effectively shielding electromagnetic waves in graphene films.
[0006] The present invention also provides a preparation method of the electromagnetic shielding graphene film material and application thereof.
[0007] Technical solution: In order to achieve the above-mentioned purpose, the present invention provides a high temperature resistant electromagnetic shielding graphene film material, which is formed by conjugated benzoxazine and graphene, and the mass ratio of graphene to conjugated benzoxazine is 2:1-1:2. The structure of the conjugated benzoxazine is as follows: .
[0008] Furthermore, the graphene is single-layer graphene.
[0009] The method for preparing the high temperature resistant electromagnetic shielding graphene film material of the present invention comprises the following steps: (1) adding an organic solvent to 2,5-dihydroxyterephthalaldehyde and 1,2,3,4-tetrahydroisoquinoline, heating the reaction, filtering the reactant, washing the filtrate, and drying the filtrate by rotary evaporation to obtain a solid product, i.e., a highly conjugated benzoxazine; (2) The prepared highly conjugated benzoxazine is mixed with a graphene dispersion and stirred, the graphene is mixed with the highly conjugated benzoxazine, and then the mixture is vacuum filtered for self-assembly, and finally heated and cured to obtain the target product, a high-temperature resistant electromagnetic shielding graphene film material.
[0010] Preferably, the method for preparing the high temperature resistant electromagnetic shielding graphene film material of the present invention comprises the following steps: In step (1), 2,5-dihydroxyterephthalaldehyde, 1,2,3,4-tetrahydroisoquinoline, 3Å molecular sieve, acetic acid and an organic solvent are added to a flask, and the mixture is reacted at 50-100° C. for 3-8 hours. After the reaction is stopped, the reactant is filtered, and the filtrate is washed with water and then rotary evaporated and dried to obtain a solid product, which is a highly conjugated benzoxazine monomer. In step (2): the prepared benzoxazine and graphene are mixed in different mass ratios, dispersed evenly, and then assembled into a thin film by vacuum-assisted self-assembly. Finally, the target product is obtained by curing and polymerization by heating.
[0011] Furthermore, in step (1), the molar ratio of 2,5-dihydroxyterephthalaldehyde to 1,2,3,4-tetrahydroisoquinoline is 1:2-3.
[0012] Preferably, the molar ratio of 2,5-dihydroxyterephthalaldehyde to 1,2,3,4-tetrahydroisoquinoline is 1:2.6.
[0013] Furthermore, the organic solvent in step (1) is selected from any one of toluene, xylene or dioxane.
[0014] Furthermore, the heating reaction temperature in step (1) is 50-100° C. and the time is 3-8 hours.
[0015] Furthermore, in step (2), the mass ratio of graphene to benzoxazine is 2:1-1:2, and the reaction is stirred at room temperature for 20-25 hours.
[0016] Preferably, the graphene dispersion in step (2) is a single-layer graphene dispersion, and the single-layer graphene dispersion is diluted before being mixed with benzoxazine, and the dilution ratio is 0.1-1 mg / mL.
[0017] Preferably, the mass ratio of graphene to benzoxazine is 2:1.
[0018] Furthermore, the vacuum filtration self-assembly in step (2) is to filter in a Büchner sand core funnel, and the film obtained after the filtration is dried in a vacuum drying oven.
[0019] Furthermore, the specific heating process of the heating and curing in step (2) is as follows: heating to 140-150°C for 1-2h, 160-170°C for 1-2h, 180-190°C for 1-2h, 200-210°C for 1-2h, 220-230°C for 1-2h, and 240-250°C for 1-2h.
[0020] Preferably, the specific heating process of the temperature-raising ring-opening polymerization is as follows: heating to 140°C for 1 hour, 160°C for 1 hour, 180°C for 1 hour, 200°C for 1 hour, 220°C for 1 hour, and 240°C for 2 hours.
[0021] The high temperature resistant electromagnetic shielding graphene film material of the present invention is used in electronic components of new energy vehicles and computer server terminal shielding materials.
[0022] Furthermore, the application is electronic components for new energy vehicles and computer server terminal shielding materials.
[0023] The benzoxazine / graphene composite film provided by the present invention has the advantages of simple and controllable preparation process, low production cost, strong interlayer bonding force, etc. Graphene and benzoxazine are assembled through conjugated physical action, and the graphene interlayer bonding force is strong. Due to the addition of graphene, the thermal properties of the benzoxazine resin, as well as its toughness, electromagnetic shielding and other properties are greatly improved.
[0024] The present invention designs a completely new resin structure, namely a benzoxazine resin with a multifunctional ring structure, and the conjugation effect brought by the π-π conjugated structure interacts with graphene, so that the resin and graphene can self-assemble. The composite material formed by the self-assembly of the resin and graphene of the present invention has a continuous phase structure and excellent electromagnetic shielding performance.
[0025] The benzoxazine resin with a high degree of conjugation designed by the present invention is used as a novel adhesive to tightly bond the graphene layers, rather than the traditional polymer-based film, and is assembled through the conjugation of the benzoxazine conjugated structure and graphene.
[0026] The present invention prepares an ultra-thin graphene / benzoxazine layer-by-layer structure film through a simple process, which has a toughness similar to that of paper and has high electromagnetic shielding and flame retardant properties. The prepared film increases the interface performance through the specific π-π conjugation of benzoxazine and graphene. At the same time, the benzoxazine with a specific structure of the present invention can repair the defects on the surface of graphene and further enhance the performance. Its special orientation structure is conducive to giving full play to the advantages of graphene in shielding electromagnetic waves, forming a stacked layered structure, and enhancing the interlayer reflection and loss of electromagnetic waves.
[0027] In the present invention, the pure graphene film prepared by the same process will crack to varying degrees due to loose bonding, and the film shielding efficiency of the present invention is relatively high; the pure benzoxazine monomer is very brittle after solidification, cannot be bent, and has very low intrinsic conductivity. In addition, the present invention affects the product effect through the raw material ratio of benzoxazine and graphene, the temperature of drying after filtration, the mixing time of graphene and benzoxazine monomer, and the temperature range of solidification. The effect of adjusting each reaction condition is not as good as the present invention, especially the ratio of benzoxazine monomer and graphene in the present invention, too much or too little benzoxazine monomer will have a significant effect on the electromagnetic interference shielding performance.
[0028] The present invention utilizes the conjugation between the benzoxazine resin and graphene with a high conjugated structure for assembly. Under vacuum assistance, graphene sheets are stacked layer by layer in a solution to form a layered structure. The resin acts as an adhesive between the graphene layers to connect the two adjacent layers of graphene sheets, so that the graphene sheets are tightly combined to construct a high-speed conductive channel and an efficient electromagnetic shielding structure. The stacked structure can enhance the scattering and reflection of electrons between layers, thereby greatly improving the electromagnetic shielding performance. At the same time, the addition of graphene can also improve the heat resistance and flame retardancy of the material.
[0029] The present invention utilizes the strong conjugation between graphene and resin for the first time, and combines the vacuum-assisted self-assembly method to construct a layered structure, which is conducive to the construction of a conductive channel. Compared with the prior art, the present invention has high electromagnetic shielding performance, toughness and excellent flame retardant performance while having an ultra-thin thickness. The combination of the polymer matrix and graphene in the present invention mainly relies on a strong conjugation, which is conducive to achieving a lower permeation threshold.
[0030] The present invention uses a benzoxazine resin of a specific structure, a raw material ratio and reaction conditions, and relies on the conjugation effect between the resin and graphene to achieve assembly. The existing high-temperature resistant graphene film materials are mainly assembled by combining DA bonds and conjugation, and their electromagnetic shielding performance is poor. The conjugation effect of the present invention is stronger in the conjugated structure. The present invention uses a very strong conjugation effect between the resin and graphene to lower the permeation threshold, thereby constructing a composite film with high electromagnetic shielding performance, which is suitable for application in server terminals, electromagnetic wave shielding of electronic components and other fields, and the high-temperature resistant graphene film material relies on the DA bond and conjugation effect between the resin and graphene to construct a heat conduction channel to prepare a high thermal conductivity film, which is suitable for application in heat dissipation, temperature control and other fields.
[0031] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: 1. The present invention assembles benzoxazine with a specific structure and graphene to prepare a film, which is prepared by vacuum filtration and has a simple process. While the graphene is stacked and assembled layer by layer, the layers are connected by benzoxazine molecules, and the orientation is good. After the electromagnetic wave enters the film, it is lost through multiple reflections and absorption, showing excellent EMI shielding performance. The film material obtained after curing has a toughness similar to that of paper.
[0032] 2. In the highly conjugated benzoxazine / graphene film system prepared by the present invention, graphene and benzoxazine are self-assembled through conjugation, so that the orientation degree of the film material is improved, giving the material excellent properties such as excellent conductivity and toughness, and the film thickness is about 50 μm. After curing, the composite material has a carbon residue rate of more than 70% at 800°C, has excellent flame retardancy, is suitable for the preparation of high-performance electromagnetic shielding materials, and has potential applications in the fields of electronic components such as integrated circuits and computer server terminal shielding. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the H NMR spectrum of the benzoxazine monomer obtained in Example 1; Figure 2 is the infrared spectrum of the benzoxazine monomer obtained in Example 1; Figure 3 is the DSC spectrum of the benzoxazine monomer obtained in Example 1; Figure 4 This is the TGA graph of the benzoxazine cured material obtained in Example 1; Figure 5 is a TGA graph of the benzoxazine / graphene composite film obtained in Example 1; Figure 6 This is a SEM image of the benzoxazine / graphene composite film obtained in Example 1; Figure 7 This is a physical picture of the benzoxazine / graphene composite film obtained in Example 1; Figure 8 This is a comparison chart of the electromagnetic shielding efficiency of the benzoxazine / graphene composite films obtained in Examples 1-4 at 8-12 GHz. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0035] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources. Experimental methods without specific conditions specified in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0036] The graphene is single-layer graphene (graphene purity>99wt%, thickness 0.5-3nm, sheet diameter 0.5-5μm, single-layer rate greater than 98%), purchased from Suzhou Carbonfeng Graphene Technology Co., Ltd., specifically the purchased graphene N-methylpyrrolidone dispersion, with a graphene concentration of 1mg / mL.
[0037] 3Å molecular sieves, purchased from Aladdin, M100321-100g.
[0038] Example 1
[0039] Preparation of high temperature resistant electromagnetic shielding graphene film materials: Step 1: 1.66 g (0.01 mmol) 2,5-dihydroxyterephthalaldehyde, 3.46 (0.026 mmol) 1,2,3,4-tetrahydroisoquinoline, 3 g 3Å molecular sieve, and 1.2 g (0.02 mmol) acetic acid were placed in a flask at room temperature, and 150 ml toluene was added. The mixture was stirred and reacted at 60°C for 3 hours. After the reaction was stopped, the reactant was filtered, the filtrate was washed with water 3 times, and then rotary evaporated. The filtrate was dried in a vacuum oven at 50°C for one day to obtain a benzoxazine monomer with a yield of about 87%. The structure is shown below: .
[0040] Step 2, at room temperature, add N-methylpyrrolidone to 20ml of graphene dispersion (1mg / ml) to dilute it to 100ml (0.2mg / ml), ultrasonically disperse it for 30min, add 40mg of benzoxazine monomer, and stir it at room temperature for 20h. After stirring, ultrasonicate the solution for 10min, then filter it in a Büchner sand core funnel for 10h by vacuum-assisted self-assembly, dry the film obtained by filtration at 80℃ in a vacuum drying oven for 20h, and finally heat it for ring-opening curing polymerization to obtain the target product. The specific heating process of the ring-opening curing polymerization is as follows: heat it to 140℃ and keep it for 1h, 160℃ and keep it for 1h, 180℃ and keep it for 1h, 200℃ and keep it for 1h, 220℃ and keep it for 1h, and 240℃ and keep it for 2h.
[0041] Figure 1 This is the H NMR spectrum of the benzoxazine monomer prepared in step (1), with characteristic peaks of the oxazine ring at chemical shifts of about 5.69 ppm and 3.81 ppm.
[0042] 1 H NMR (400 MHz, CDCl3): 7.41 (m, 2H), 7.30 (m, 4H), 7.22 (m, 2H), 6.54 (s, 2H), 5.69 (s, 2H), 4.53 (d, 2H), 3.81 (d, 2H), 3.37 (s, 2H), 3.11(s, 2H), 2.95(s, 2H), 2.84(s, 2H).
[0043] Figure 2 This is the infrared spectrum of the benzoxazine monomer prepared in step (1), where 1217 and 908 cm -1 It is the characteristic peak of oxazine ring.
[0044] Figure 3 The DSC graph of the benzoxazine monomer prepared in step (1) obtained by differential scanning calorimetry shows that the starting temperature of the thermal ring-opening polymerization of the monomer is 215°C, and the peak value of the polymerization exothermic peak appears at 238°C.
[0045] Figure 4 The TGA graph of the benzoxazine monomer prepared in step (1) after curing (the curing method is the same as that in step 2, except that no graphene is added) shows that the 5% thermal weight loss temperature is 273°C, and the residual carbon rate at 800°C is 33%.
[0046] Figure 5 This is the TGA graph of the final product benzoxazine / graphene film prepared in step (2), the 5% thermal weight loss temperature is 344°C, the 10% thermal weight loss temperature is 388°C, the residual carbon rate at 800°C is about 72%, and the electrical conductivity is 737 S / m.
[0047] Figure 6 The film prepared in this example was observed to have a relatively regular layer-by-layer stacking structure through SEM testing.
[0048] Figure 7 This is a real-life effect diagram of the film prepared in this embodiment. The film thickness is about 50 μm. Different from the existing graphene or benzoxazine films with poor toughness, the film of the present invention can be bent like paper.
[0049] Example 2
[0050] Preparation of high temperature resistant graphene film materials: 1. At room temperature, 1.66 g (0.01 mmol) of 2,5-dihydroxyterephthalaldehyde, 3.46 (0.026 mmol) of 1,2,3,4-tetrahydroisoquinoline, 3 g of 3Å molecular sieves, and 1.2 g (0.02 mmol) of acetic acid were placed in a flask, and 150 ml of dioxane was added. The mixture was stirred and reacted at 100°C for 5 hours. After the reaction was stopped, the reactant was filtered, the filtrate was washed with water for 3 times, and then rotary evaporated, and dried in a vacuum drying oven at 50°C for one day to obtain a benzoxazine monomer with a yield of about 77%.
[0051] 2. At room temperature, add N-methylpyrrolidone to 20 ml of graphene dispersion (1 mg / ml) to dilute it to 100 ml (0.2 mg / ml), and after 40 minutes of ultrasonic dispersion, add 20 mg of benzoxazine monomer and stir at room temperature for 20 hours. After stirring, ultrasonicate the solution for 8 minutes, and then filter it in a Büchner sand core funnel for 10 hours by vacuum-assisted self-assembly. The film obtained by filtration is dried at 80°C in a vacuum drying oven for 20 hours, and finally heated to open-ring curing polymerization to obtain the target product. The specific heating process of the temperature-raising ring-opening curing polymerization is as follows: heat up to 140°C for 1 hour, 160°C for 1 hour, 180°C for 1 hour, 200°C for 1 hour, 220°C for 1 hour, and 240°C for 2 hours.
[0052] The benzoxazine / graphene film prepared in this embodiment has a 5% thermal weight loss temperature of 358°C, a 10% thermal weight loss temperature of 394°C, a carbon residue rate of about 75% at 800°C, and an electrical conductivity of 903 S / m.
[0053] Example 3
[0054] 1. At room temperature, 1.66 g (0.01 mmol) of 2,5-dihydroxyterephthalaldehyde, 3.46 (0.026 mmol) of 1,2,3,4-tetrahydroisoquinoline, 3 g of 3Å molecular sieves, and 1.2 g (0.02 mmol) of acetic acid were placed in a flask, and 150 ml of xylene was added. The mixture was stirred and reacted for 8 hours at 50°C. After the reaction was stopped, the reactant was filtered, the filtrate was washed with water 3 times, and then rotary evaporated, and dried in a vacuum drying oven at 50°C for one day to obtain a benzoxazine monomer with a yield of about 88%.
[0055] 2. At room temperature, add N-methylpyrrolidone to 20 ml of graphene dispersion (1 mg / ml) to dilute it to 100 ml (0.2 mg / ml), and after ultrasonic dispersion for 30 minutes, add 10 mg of benzoxazine monomer and stir at room temperature for 20 hours. After stirring, ultrasonicate the solution for 10 minutes, and then filter it in a Büchner sand core funnel for 10 hours by vacuum-assisted self-assembly. The film obtained by filtration is dried at 80°C in a vacuum drying oven for 20 hours, and finally heated to open-ring curing polymerization to obtain the target product. The specific heating process of the temperature-raising ring-opening curing polymerization is as follows: heat up to 140°C for 1 hour, 160°C for 1 hour, 180°C for 1 hour, 200°C for 1 hour, 220°C for 1 hour, and 240°C for 2 hours.
[0056] The benzoxazine / graphene film prepared in this embodiment has a 5% thermal weight loss temperature of 361°C, a 10% thermal weight loss temperature of 403°C, a carbon residue rate of about 78% at 800°C, and an electrical conductivity of 985 S / m.
[0057] Example 4
[0058] Example 4 The same method as Example 3 was used, except that N-methylpyrrolidone was added to 21 ml of graphene dispersion (1 mg / ml) to dilute it to 100 ml (0.21 mg / ml), and after 30 minutes of ultrasonic dispersion, 14 mg of benzoxazine monomer was added. The benzoxazine / graphene film prepared in this example had a 5% thermal weight loss temperature of 360 ° C, a 10% thermal weight loss temperature of 411 ° C, a carbon residue rate of about 80% at 800 ° C, and a conductivity of 955 S / m.
[0059] Figure 8 The electromagnetic interference shielding effectiveness diagram of the films prepared in Examples 1-4, the test conditions of which are: using a network analyzer (Agilent Technologies N5244A) to obtain electromagnetic parameters at room temperature at a frequency of 8.2-12.4 GHz (x-band). The SET average value of Example 1 is 40.5 dB, the SET average value of Example 2 is 59.3 dB, the SET average value of Example 3 is 64.1 dB, and the SET average value of Example 4 is 53.8 dB.
[0060] Comparative Example 1
[0061] Comparative Example 1 adopts the same preparation method as Example 3, except that the benzoxazine monomer is not added in step 2. The pure graphene film prepared in Comparative Example 1 will crack to varying degrees due to loose bonding, and cannot be formed into a film to test conductivity and electromagnetic shielding effectiveness, so the comprehensive performance is obviously inferior to the film prepared in Example 1 of the present invention.
[0062] Comparative Example 2
[0063] Comparative Example 2 adopts the same preparation method as Example 3, except that graphene is not added in step 2. The pure benzoxazine monomer prepared in Comparative Example 2 is very brittle after curing, cannot be bent, has very low intrinsic conductivity, and has a conductivity of only 3.71×10-15 S / m, and does not have electromagnetic shielding performance.
[0064] Comparative Example 3
[0065] Comparative Example 3 adopts the same preparation method as Example 3, except that the mass ratio of graphene to benzoxazine monomer is 1:3. The prepared film has an electrical conductivity of 483 S / m. Using the test conditions of Example 4, the average electromagnetic shielding effectiveness is 16 dB.
[0066] Comparative Example 4
[0067] Comparative Example 4 adopts the same preparation method as Example 3, except that the mass ratio of graphene to benzoxazine monomer is 3:1, and film formation is not easy due to the reduced amount of monomer added.
[0068] Comparative Example 5
[0069] The high temperature resistant graphene film material prepared by the optimal embodiment 1 in the prior art Chinese patent CN117004179A was tested for conductivity and electromagnetic interference shielding effectiveness, and its conductivity was 588 S / m. Using the test conditions of embodiment 4, the average electromagnetic shielding effectiveness was 24.9 dB.
[0070] Comparative Example 6
[0071] The conductivity of the benzoxazine resin-based graphene film prepared by the best embodiment 1 in the prior art Chinese patent CN116987362A is about 164 S / m (1.64S / cm), which is significantly lower than the material prepared by the present invention.
Claims
1. A high temperature resistant electromagnetic shielding graphene film material, characterized in that: It is formed by conjugated benzoxazine and graphene, the mass ratio of graphene to conjugated benzoxazine is 2:1-1:2, and the structure of the conjugated benzoxazine is as follows: 。 2. The high temperature resistant electromagnetic shielding graphene film material according to claim 1, characterized in that: The graphene is single-layer graphene.
3. A method for preparing the high temperature resistant electromagnetic shielding graphene film material according to claim 1, characterized in that: The steps include: (1) adding an organic solvent to 2,5-dihydroxyterephthalaldehyde and 1,2,3,4-tetrahydroisoquinoline, heating the reaction, filtering the reactant, washing the filtrate, and drying the filtrate by rotary evaporation to obtain a solid product, i.e., a highly conjugated benzoxazine; (2) The prepared highly conjugated benzoxazine is mixed with a graphene dispersion and stirred, the graphene is mixed with the highly conjugated benzoxazine, and then the mixture is vacuum filtered for self-assembly, and finally heated and cured to obtain the target product, a high-temperature resistant electromagnetic shielding graphene film material.
4. The preparation method according to claim 3, characterized in that: In step (1), the molar ratio of 2,5-dihydroxyterephthalaldehyde to 1,2,3,4-tetrahydroisoquinoline is 1:2-3.
5. The preparation method according to claim 3, characterized in that: The organic solvent in step (1) is selected from any one of toluene, xylene or dioxane; the heating reaction temperature is 50-100° C. and the time is 3-8 hours.
6. The preparation method according to claim 3, characterized in that: Step (1) also includes 3Å molecular sieves and acetic acid.
7. The preparation method according to claim 3, characterized in that: In step (2), the mass ratio of graphene to highly conjugated benzoxazine is 2:1-1:2, and the reaction is stirred at room temperature for 20-25 hours.
8. The preparation method according to claim 3, characterized in that: The vacuum filtration self-assembly in step (2) is to filter in a Büchner sand core funnel, and the film obtained after the filtration is dried in a vacuum drying oven.
9. The preparation method according to claim 3, characterized in that: The specific heating process of the heating and curing in step (2) is as follows: heat up to 140-150°C for 1-2h, 160-170°C for 1-2h, 180-190°C for 1-2h, 200-210°C for 1-2h, 220-230°C for 1-2h, and 240-250°C for 1-2h.
10. Application of the high temperature resistant electromagnetic shielding graphene film material according to claim 1 in electronic components of new energy vehicles and computer server terminal shielding materials.
Citation Information
Patent Citations
Benzoxazine resin-based graphene film material as well as preparation method and application thereof
CN116987362A
High-temperature-resistant graphene film as well as preparation method and application thereof
CN117004179A